DINAMIKA DIGITAL BUDAYA DAN PERGESERAN IDENTITAS GENERASI MUDA DALAM PERSPEKTIF POSTMODERNISME - Etti Herawati; Saslim; Rahmat Hidayat; A. Muh. Fiqri La Ali Akbar (STKIP Subang, 2026)
The development of digital technology has brought significant changes to the social lives of young people, particularly in the process of identity formation in the era of digital culture. Social media platforms such as Instagram, TikTok, YouTube, and X have become new spaces for young people to interact, express themselves, and build virtual social existence. This study aims to analyze the dynamics of digital culture and the shifting identity of young people from a postmodernism perspective. The research uses a descriptive qualitative method with a literature study approach through the examination of various books, scientific journals, and articles.The results of the study show that digital culture has changed communication patterns, lifestyles, and the ways young people construct their social identities. Youth identities have become more fluid, flexible, plural, and influenced by digital symbols and popular culture on social media. This study concludes that digital culture has a significant influence on the transformation of youth identity in the postmodern era through media domination, symbolic consumption, and the development of digital technology in contemporary society.